Pd-catalyzed ligand-free C(5)–H arylation of 1, 4-disubstituted 1, 2, 3-triazoles promoted by microwaves. Issue 20 (17th October 2016) - Zhao, Fen; Tian, Wen-Hai; Luo, Fang; Cheng, Hui-Ling; Jiang, Yu-Bo; Chen, Zhen
ABSTRACT: Pd(OAc)2 -catalyzed regioselective C(5)–H arylation of 1, 4-disubstituted 1, 2, 3-triazoles was achieved without ligand under microwave conditions in 1 h, generating 1, 4, 5-trisubstituted 1, 2, 3-triazoles with good to excellent yields. The obtained molecules can be easily converted into 4, 5-disubstituted 1, 2, 3-triazoles through the debenzylation process with one-pot manipulation. GRAPHICAL ABSTRACT: